La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism